Laser iridotomy to treat uveitis‐glaucoma‐hyphema syndrome secondary to reverse pupillary block in sulcus‐placed intraocular lenses: Case series. Issue 10 (October 2015) - Singh, Harmanjit; Modabber, Milad; Safran, Steven G.; Ahmed, Iqbal Ike K.
Abstract : Purpose : To present cases of uveitis‐glaucoma‐hyphema (UGH) syndrome due to reverse pupillary block in sulcus‐placed posterior chamber intraocular lenses (PC IOLs) that were managed with laser peripheral iridotomy (LPI). Setting : Community‐based subspecialty clinics. Design : Retrospective interventional case series. Methods : A chart review of patients with a sulcus‐placed PC IOLs presenting with UGH syndrome and reverse pupillary block with posterior iris bowing as diagnosed by gonioscopy and anterior segment optical coherence tomography was carried out. Laser peripheral iridotomy was performed in the eyes included in the study. The main outcome measure was clinical resolution of UGH syndrome. Results : The study included 6 eyes of 6 patients with a mean age of 59.8 years (range 43.0 to 66.0 years) who presented with unilateral UGH syndrome a mean of 28.7 months (range 0.3 to 84.0 months) after PC IOL implantation. All patients were previously myopic, with 5 (83.3%) having a history of vitrectomy. The mean axial length was 27.0 mm ± 1.4 (SD). An LPI was used to treat the reverse pupillary block with resultant improvement in iris profile and resolution of UGH syndrome in all eyes. The mean intraocular pressure decreased from 30.5 ± 10.0 mm Hg on 0.5 ± 0.8 glaucoma medications to 15.5 ± 3.2 mm Hg postoperatively on 0.7 ± 1.2 medications. Conclusions : The UGH syndrome due to reverse pupillary block occurred after sulcus‐placed PC IOLs in susceptible patients, those with axial myopia, and post‐vitrectomized eyes. The cases were managed with LPIs. Financial Disclosure : Dr. Ahmed is a consultant to Alcon Laboratories, Inc. and Abbott Medical Optics, Inc. No author has a financial or proprietary interest in any material or method mentioned.